2015
DOI: 10.1038/srep12948
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up assembly of metallic germanium

Abstract: Extending chip performance beyond current limits of miniaturisation requires new materials and functionalities that integrate well with the silicon platform. Germanium fits these requirements and has been proposed as a high-mobility channel material, a light emitting medium in silicon-integrated lasers, and a plasmonic conductor for bio-sensing. Common to these diverse applications is the need for homogeneous, high electron densities in three-dimensions (3D). Here we use a bottom-up approach to demonstrate the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…have proposed a MBE based bottom-up approach to produce n -type metallic Ge layers with electrically active carrier concentrations as high as 1.9 × 10 20  cm −3 and 0.9 × 10 20  cm −3 in the bi-layer and multi-layer sample, respectively1920. The recent progress in the n -type doping in Ge is summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…have proposed a MBE based bottom-up approach to produce n -type metallic Ge layers with electrically active carrier concentrations as high as 1.9 × 10 20  cm −3 and 0.9 × 10 20  cm −3 in the bi-layer and multi-layer sample, respectively1920. The recent progress in the n -type doping in Ge is summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Ge films are obtained by the molecular beam epitaxy in a bottom up approach, where nearly-identical twodimensional phosphorus doped layers are repeatedly stacked at short distances in the third, vertical dimension. Previous studies based on the anisotropic quantum interference electrical measurements, atom probe tomography, and density functional theory 23 have shown that the multi-layered doped region can be interpreted as a 3D volume of precisely defined thickness h where electrons coming from the 2D donorcontaining layers can freely move, thus realizing a 3D metallic conductor with the homogenous electron density n e .…”
Section: à3mentioning
confidence: 99%
“…Basic theory of solid-state solutions tells us that active dopants are those that substitute to Ge in a lattice position, while donor atoms that occupy interstitial sites or phase-separate into clusters are usually inactivated. It is well known that at high doping levels other effects take place, among them dopant-dimer formation 32 , increase of the dislocation density and clustering of dopants around crystal defects 33 . All these effects contribute to the decrease of N A /[P ].…”
Section: Growth Of Heavily Doped Filmsmentioning
confidence: 99%